Passive tumor targeting and imaging by using mercaptosuccinic acid-coated near-infrared quantum dots - Lin, Guimiao (2015)
In this paper, we demonstrate the preparation of monodispersed quantum dots (QDs) as near-infrared (NIR) optical probes for in vivo pancreatic cancer targeting and imaging. The design of these luminescent probes involves functionalizing NIR QDs with ligand mercaptosuccinic acid (MSA), which targets the tumor site by enhanced permeability and retention effect. The colloidal and optical stability of the QDs can be maintained for >1 week. In vivo optical imaging studies in nude mice bearing pancreatic tumor show that the probes accumulate at tumor sites for >2.5 hours following intravenous injection of the functionalized NIR QDs. Tumor-labeling studies showed no evidence of harmful effects on the treated animals, even at a dose as high as ~50 mg/kg. These results demonstrate that the engineered MSA-functionalized QDs can serve as a diagnostic platform for early detection of cancer, as well as in image-guided precise surgical resection of tumors.